IMPLEMENTASI KEBIJAKAN SISTEM PENGAWASAN BANK INDONESIA PADA AKTIVITAS USAHA MONEY CHANGER DI KABUPATEN BADUNG - Putu Eka Purnamaningsih; Kadek Wiwin Dwi Wismayanti (Jurnal Ilmiah Cakrawarti, 2021)
Badung regency is in the first place with the most Money Changer business in Bali, which is 446 units or with a percentage of about 70% of the total money changer business in Bali. Of the many business units of Money Changer, in the implementation of its activities are still encountered problems such as unlicensed Money Changer still found, the existence of fraud related to money changer business, and the lack of public understanding related to Money Changer certified and not. The purpose of this research is to determine the implementation of  regulations of Bank Indonesia as an independent institution that has authority in carrying out payment system supervision on rupiah, one of which is non-bank foreign exchange business activities. Data is collected by observation method, semistructure interview and documentation. Based on the research using Implemetation Theory according to Charles o Jones, the results showed that there are several indicators that have been well met as well as indicators of Productivity, Accountability, Service Quality, and Responsibiltas. While the Responsiveness indicator shows good results but is not optimal, the shortcomings are largely due to lack of socialization, onsite or direct supervision, and human resources as well as lack of cooperation activities with basic-level organizations to carry out direct supervision.